The phantom twin - Brown, Lisa, 1972- (First Second, 2020)
Full-color graphic novel featuring a pair of conjoined twins named Jane and Isabel Peabody, who have been part of a traveling circus since they were three. Seeking freedom and the possibility of marriage, Jane agrees to an experimental separation surgery. Isabel dies but attaches herself as a ghost to Jane, who struggles with Isabel's loss, getting fired from the circus, and finding a new life of independence.